Comparative anatomy of the prosubiculum, subiculum, presubiculum, postsubiculum, and parasubiculum in human, monkey, and rodent - Ding, Song-Lin (Journal of comparative neurology (1911), 2013)
ABSTRACT The subicular complex, including the prosubiculum (ProS), subiculum (Sub), presubiculum, postsubiculum (PoS), and parasubiculum (PaS), plays important roles in the medial temporal memory system and is heavily involved in many neurological diseases such as Alzheimer's disease and epilepsy. In the literature, the ProS (in primate) and PoS (in rodent) are inconstantly identified, making data comparison difficult across species. This review is an attempt to discuss equivalencies and extent of the five subicular components in human, monkey, and rodent based on available information on their cytoarchitecture, chemoarchitecture, molecular signature, and neural connectivity. All five subicular cortices exist in human, monkey, and rodent. In human and monkey, the ProS and Sub extend into the uncal region anteriorly, and the PoS and PaS reach the cingulate isthmus posteriorly. In rodent, most of the typical subicular cortices are located in the dorsal and caudal portions of the hippocampal formation, and the modified version of the ventral ProS and Sub corresponds to the modified description of the uncal ProS and Sub in monkey and human. An interesting triangular region in rodent located at the juncture of the PoS, PaS, retrosplenial cortex, and visual cortex appears to be the equivalent of the monkey area prostriata. Major connections of the five subicular cortices are also summarized based on unified criteria discussed in this review, with distinct connections revealed between the ProS and the Sub. J. Comp. Neurol. 521:4145–4162, 2013. © 2013 Wiley Periodicals, Inc. Based on conserved gene expression patterns, and other anatomical features, the author compares five subicular regions in human, monkey and rodent. Previously ignored rodent prosubiculum, and modified subiculum (Sub') and prosubiculum (ProS') in the three species were identified. These findings will make data comparison and analysis much easier across species.